Pengaruh Metode Role Playing Terhadap Keterampilan Berbicara Siswa Kelas V SD Negeri 37 Pekanbaru - Kurniaman, Otang; Witri, Gustimal; Utami, Sholiha Dwi (Lembaga Yasin AlSys, 2023)
This study aims to determine the effect of the role playing method on speaking skills of fifth grade students at SD Negeri 37 Pekanbaru. This type of research is quantitative research using pre-experimental design methods. The research design used in this study is the one group pretest posttest design. The subject of this study were students of class V B at SD Negeri 37 Pekanbaru with a total of 23 students. The data collection technique used in this research is using an oral test through the initial test technique (pretest) and the final test (posttest). the results of this study show that students speaking skills have increased. The average pretest score obtained was 40,86 then given treatment eith the role playing methode after being given posttest further treatment, the average posttest score increassed to 64,13 and obtained an increase (gain) of 0,38 with moderate criteria. Based on the result of the research and data analysis, it can be concluded that the role playing method has an effect on the speaking skills of fifth frade students at SD Negeri 37 Pekanbaru. Based on the result of the t_table that has been carried out, a significance of 8.21 is greater than t_table 2.08 it can be concluded that H_o is rejected and H_a is accepted.